2013
DOI: 10.1371/journal.pone.0070112
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Effects of Two Neonicotinoid Insecticides on Mouse Sperm Function and Early Embryonic Development In Vitro

Abstract: Acetamiprid (ACE) and imidacloprid (IMI) are two major members in the family of neonicotinoid pesticides, which are synthesized with a higher selectivity to insects. The present study determined and compared in vitro effects of ACE, IMI and nicotine on mammalian reproduction by using an integrated testing strategy for reproductive toxicology, which covered sperm quality, sperm penetration into oocytes and preimplantation embryonic development. Direct chemical exposure (500 µM or 5 mM) on spermatozoa during cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(60 citation statements)
references
References 29 publications
1
53
1
2
Order By: Relevance
“…In recent years, many scientific studies indicated toxicity of IM on mammalian system such as teratogenic, mutagenic, neurotoxic, and immunotoxic effects (Duzguner and Erdogan, ; Gawade et al, ; Lonare et al, ). In addition, it has been reported that acetamiprid and IM exposure under in vitro system adversely alters the mouse sperm function and early embryonic development (Gu et al, ) and induces morphological and DNA damage on the reproductive organs of developing male rats (Bal et al, ). Furthermore, gestational exposure to IM altered the neurobehavior of young ones included fetal deformities (Gawade et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many scientific studies indicated toxicity of IM on mammalian system such as teratogenic, mutagenic, neurotoxic, and immunotoxic effects (Duzguner and Erdogan, ; Gawade et al, ; Lonare et al, ). In addition, it has been reported that acetamiprid and IM exposure under in vitro system adversely alters the mouse sperm function and early embryonic development (Gu et al, ) and induces morphological and DNA damage on the reproductive organs of developing male rats (Bal et al, ). Furthermore, gestational exposure to IM altered the neurobehavior of young ones included fetal deformities (Gawade et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Pesticides are widely used and readily detected in the environment, thus posing risks to human health (Weichenthal et al 2012). Neonicotinoids, which have been increasingly used in recent decades, induce developmental neurotoxicity, reproductive defects, and embryo toxicity through various toxicity pathways based on both in vitro and in vivo results (Babelova et al 2017, Gu et al 2013, Kimura-Kuroda et al 2012). However, the epigenetic effects of neonicotinoids such as DNA methylation on developmental toxicity are not well studied.…”
Section: Discussionmentioning
confidence: 99%
“…These findings unveiled the hazardous effects of neonicotinoid insecticides exposure on mammalian sperm fertilization ability as well as embryonic development, raising the concerns that neonicotinoid insecticides may pose reproductive risks on human reproductive health, especially in professional populations. 13 Acetamiprid is also having most devastating effect causing erectile dysfunction as it acts through multiple inhibitory pathways. 14 Emamectin benzoate is a biopesticide derivative of the avermectins developed for the control of insect pests.…”
Section: Discussionmentioning
confidence: 99%